2012
DOI: 10.1111/j.1742-4658.2012.08557.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug target validation of the trypanothione pathway enzymes through metabolic modelling

Abstract: A kinetic model of trypanothione [T(SH) 2 ] metabolism in Trypanosoma cruzi was constructed based on enzyme kinetic parameters determined under near-physiological conditions (including glutathione synthetase), and the enzyme activities, metabolite concentrations and fluxes determined in the parasite under control and oxidizing conditions. The pathway structure is characterized by a T(SH) 2 synthetic module of low flux and low catalytic capacity, and another more catalytically efficient T(SH) 2 -dependent antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 83 publications
5
44
0
1
Order By: Relevance
“…In addition, a previous report describing kinetics of T(SH) 2 biosynthesis in Trypanosoma cruzi [80] also supports the role of γ -GCS and TryS proteins in counteracting oxidative stress conditions. This study suggested that main control flux is regulated by γ -GCS and TryS proteins, followed by spermidine transporter, TryR and T(SH) 2 -dependent thiol pathway enzymes [80]. CS may also play a crucial role in regulating the T(SH) 2 biosynthesis pathway because it provides cysteine for the biosynthesis of γ -glutamylcysteine and glutathione by γ -GCS and glutathione synthetase enzymes, respectively [6].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In addition, a previous report describing kinetics of T(SH) 2 biosynthesis in Trypanosoma cruzi [80] also supports the role of γ -GCS and TryS proteins in counteracting oxidative stress conditions. This study suggested that main control flux is regulated by γ -GCS and TryS proteins, followed by spermidine transporter, TryR and T(SH) 2 -dependent thiol pathway enzymes [80]. CS may also play a crucial role in regulating the T(SH) 2 biosynthesis pathway because it provides cysteine for the biosynthesis of γ -glutamylcysteine and glutathione by γ -GCS and glutathione synthetase enzymes, respectively [6].…”
Section: Discussionsupporting
confidence: 65%
“…This suggests that either these isolates are different or canine isolated parasites differ from human isolates because antimony resistant isolates reported so far showed up-regulation of cytosolic isoforms of TXN and TXNPx [77], [78], [79]. In addition, a previous report describing kinetics of T(SH) 2 biosynthesis in Trypanosoma cruzi [80] also supports the role of γ -GCS and TryS proteins in counteracting oxidative stress conditions. This study suggested that main control flux is regulated by γ -GCS and TryS proteins, followed by spermidine transporter, TryR and T(SH) 2 -dependent thiol pathway enzymes [80].…”
Section: Discussionmentioning
confidence: 71%
“…Our polyamine model complements a recent attempt at modelling trypanothione () metabolism in the related parasite T. cruzi [6]. The T. cruzi model focuses on the glutathione synthesis branch and the redox cycle of .…”
Section: Discussionmentioning
confidence: 99%
“…These features have ensured that the polyamine pathway in T. brucei has been subject to investigation and details are available for enough of the enzymes to allow a mathematical model to be constructed. A recent attempt to model trypanothione () metabolism in Trypanosoma cruzi ( T. cruzi ) [6] also points to the value in modelling of this branch of metabolism in trypanosomatids.…”
Section: Introductionmentioning
confidence: 99%
“…Polyamines are positively charged, flexible hydrocarbons that are essential for growth and proliferation of eukaryotic cells, with roles in transcription, translation, chromatin structure, and ion channel function (7)(8)(9)(10). Trypanosomes have evolved to use the polyamine spermidine in an additional role through conjugation with two molecules of glutathione to form the essential redox cofactor trypanothione [N1,N8-bis(glutathionyl)-spermidine] (11).…”
Section: T Rypanosoma Brucei Is the Causative Agent Of Human African mentioning
confidence: 99%